2020
DOI: 10.1364/oe.390209
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-principle demonstration of compiled Shor’s algorithm using a quantum dot single-photon source

Abstract: We report a proof-of-principle demonstration of Shor's algorithm with photons generated by an on-demand semiconductor quantum dot single-photon source for the first time. A fully compiled version of Shor's algorithm for factoring 15 has been accomplished with a significantly reduced resource requirement that employs the four-photon cluster state. Genuine multiparticle entanglement properties are confirmed to reveal the quantum character of the algorithm and circuit. The implementation realizes the Shor's algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Construction of 15A Factoring circuit with (a, N ) = (7, 15) is traditionally discussed in Vandersypen et al [34] and recently, Monz et al [12] and Duan et al [45] reported experiments with using semi-classical QFT. Our circuit (Figure 15) follows [34].…”
Section: F Construction Of Our Factoring Circuitsmentioning
confidence: 99%
“…Construction of 15A Factoring circuit with (a, N ) = (7, 15) is traditionally discussed in Vandersypen et al [34] and recently, Monz et al [12] and Duan et al [45] reported experiments with using semi-classical QFT. Our circuit (Figure 15) follows [34].…”
Section: F Construction Of Our Factoring Circuitsmentioning
confidence: 99%
“…However, recent advances in computational resources and quantum computing, may potentially jeopardize these cyrptobased solutions [145][146][147][148]. This has motivated the community to explore alternative approaches, a popular one is: Physical Layer Security.…”
Section: A a Primer On Information Securitymentioning
confidence: 99%
“…The construction of U f is the most challenging part when implementing Shor's algorithm. It is usually based on controlled modular multiplier blocks, individually designed for each choice of a and M [63,64]. In terms of tensor products, however, we can construct an explicit representation for any base and modulus.…”
Section: Shor's Algorithmmentioning
confidence: 99%